Rituximab and its therapeutic potential in catastrophic antiphospolipid syndrome. (February 2015) - Rodríguez-Pintó, Ignasi; Cervera, Ricard; Espinosa, Gerard
The catastrophic antiphospholipid syndrome (CAPS) is characterized by thrombosis in more than three organs or systems developing over a short period of time. Despite conventional treatment with a combination of anticoagulation plus corticosteroids plus plasma exchange, and/or intravenous immunoglobulin, mortality remains high and some patients suffer from recurrent CAPS episodes. In selected patients, new therapies such as rituximab may be a treatment option. In this review, the rationale for using rituximab in CAPS is discussed.